The Influence Of Training And Competence On Performance At PT. Telkom Indonesia - Rini Tri Apriliani; Masydzulhak Djamil Mz (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
This study aims to determine the effect of competence and training on the performance of employees of PT. Telkom Indonesia with career path as an intervening variable. In this study, the population taken were employees of PT. Telkom Indonesia. The sampling in this study was carried out using purposive sampling method. This study used as many as 50 samples. The researcher applies the SmartPLS data analysis technique. After the research results are obtained, it can be seen that competence affects performance, training affects performance, career path affects performance, competence affects career path, training affects career path, career path has a weak influence on performance.